Contribution quality evaluation of table tennis match by using TOPSIS-RSR method - an empirical study - Yin, H.; Chen, X.; Zhou, Y.; Xu, J.; Huang, D. (BMC Sports Science, Medicine and Rehabilitation, 2023)
This paper aims to evaluate the contribution quality of table tennis matches comprehensively and explore the ranking characteristics of evaluation results and the rationality of grading. Through the application of the documentation method, videos, Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Rank Sum Ratio (RSR), the contribution quality evaluation index system of table tennis matches was established. After then, the technical and tactical performances of 38 matches between H (anonymous), who is currently highly concerned and active in the international table tennis world from 2018 to 2020 were comprehensively evaluated. According to research results, H had 8 matches with the Ci value > 0.5 in serve rounds, 4 with the Ci value > 0.5 in receive rounds, and 5 with the RSR value > 0.6 in the comprehensive strength. These findings were generally consistent with the final match results. Furthermore, Pearson Correlation showed that the three indicators were significantly correlated with competition performance (CP) (P < 0.01). Each race could be divided into four grades, and there was a very significant difference among them by variance test (F = 60.281, P < 0.01). Meanwhile, SNK pairwise comparison between four grades had statistical significance (P < 0.05). Therefore, researchers could conclude that the combination of TOPSIS and RSR could objectively and accurately reflect the contribution quality of table tennis matches. This method could be promoted and applied in the competition performance evaluation of other net games.